Analysis of sand slopes stabilized with facing of soil bags with extended reinforcement strips. Issue 4 (1st August 2008) - Tatsuoka, F.; Mohri, Y.; Matsushima, K.; Huang, C.-C.
Abstract : A limit-equilibrium-based stability analysis method was developed to simulate the stability of unreinforced sand slopes and geosynthetic-reinforced sand slopes that had been stabilized with soil bags stacked on the slope face. The stability of unreinforced and reinforced sand slopes when loaded with a rigid strip footing placed on the slope crest was evaluated by performing physical model tests. The stabilizing effects of an inclined stacked soil bag facing with extended reinforcement strips (tails) were confirmed. The results of limit-equilibrium analyses showed good agreement with the physical model test results. A parametric study performed using the proposed method also revealed that the effects of the soil bag inclination angle, αb, and internal friction angle of the backfill soil, ϕs, on the slope stability of the unreinforced and reinforced sand slopes are significant. The ultimate footing loads observed in five physical model tests on reinforced and unreinforced slopes can be simulated by the proposed analysis method when using a single 'operational' friction angle (ϕop ) that is 82 to 86% of the peak internal friction angle obtained from conventional drained plane strain compression tests (namely, ϕp ) under low pressure levels as in the unloaded model slope. This ratio of ϕop /ϕp is consistent with the value found in stability analyses of reinforced and unreinforced shallow sand slopes reported in the literature.